The ensemble practice : a team-based approach to building a superior wealth management firm - Palaveev, Philip, 1973- (Bloomberg financial series., 2013)
A detailed road map for wealth managers who want to build an ensemble firm or team and achieve sustained growth, profitability and high valuationsWhy do ten percent of wealth management firms grow faster than the rest of the industry, often despite the turbulence of the markets' The answer, according to industry consultant and researcher, P. Palaveev, is that the most successful firms are those which, create and promote a team-based service model that serves as the foundation of their enterprise. Find out how and why a team-based service model can play a decisive role in the future growth and sustained success of your wealth management firmDiscover the key factors for building a successful ensemble firm and profit from the best practices top team-based firms employProfit from the author's years of experience working with the world's top wealth management firms and the data he has compiled as a pre-eminent industry researcherLearn about the various organizational structures, partnership models and career path options and how to put them to work building an ensemble practiceGet the lowdown on how the savviest traditional broker-dealer firms have formed dynamic ensemble teams within their organizations and learn of the results they've achieved.